Different element/Ca ratios in the otolith of cultured sea bass in Malaysia and relationship to salinity - Afiza Suriani Sarimin; Che Abd Rahim Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2013)
The otoliths of cultured sea bass (Lates calcarifer) were sampled from 24 locations in Malaysian coastal waters in order to analyse the ratio values of Sr/Ca, Mg/Ca, Ba/Ca and Zn/Ca. Then the ratio values were discriminated to reconstruct a reliable marker for the migration of wild sea bass. Cultured sea bass was collected from cages and ponds along Malaysian coastal areas from March 2007 to May 2009 with ambient water salinity from oligohaline (0.1 psu) to euhaline (30-35 psu). The study found that the ratios of Mg/Ca and Zn/Ca in cultured sea bass otoliths were not influenced by the variation in water salinity. However, contradictory pattern value ratios of Ba/Ca in sea bass otoliths were found for the thalassic series. The oligohaline waters were shown to have the highest Ba/Ca ratio with the exception of Sr/Ca ratios in saline waters. This indicates that the concentration of the Sr element is slightly dominant in the otolith whereas the content of Ba was significant with salinity values. The Partition Coefficient (DMe) value also supports the proposition that the Ba element is a good tracer for salinity fluctuations in the otolith as shown by the sea bass migration track along the salinity gradient according to thalassic series.